The association between COVID-19 WHO non-recommended behaviors with psychological distress in the UK population: A preliminary study. (November 2020) - Ben-Ezra, Menachem; Cary, Neil; Goodwin, Robin
Abstract: The novel Coronavirus COVID-19 has led the WHO to warn of the risk of potentially disruptive behaviors. However, the association between maladaptive actions and mental health has not been empirically assessed. A national study of 1293 participants from the UK recorded location, underlying medical conditions and non-recommended behaviors along with psychological distress. Elevated psychological distress was associated with living in London, underlying medical conditions and practicing non-recommended behaviors. Findings suggest that medical authorities should address the association between psychological distress and adoption of potentially maladaptive behaviors.